The differences between Froriepia subpinnata (Ledeb.) Baill. and Pimpinella anisum L. commonly named as anarijeh based on major components of the essential oil; a marker for resolve ambiguities - Pooyan Mehrabanjoubani; Majid Ghorbani Nohooji; Ehsan Karimi; Ahmad Abdolzadeh (Institue of Medicinal Plants, ACECR, 2021)
Background: Froriepia subpinnata (Ledeb.) Baill. and Pimpinella anisum L. are two important medicinal plants belong to the Apiaceae family. Due to the similar Persian name in ethnobotanical studies, namely "anarijeh", these two medicinal plants are mistakenly used instead of each other in the Iranian medicinal plants market and even in scientific reports. Objective: In this study, the correct morphological description of studied species were introduced and the chemical composition of their essential oils and their antioxidant activities were determined. Methods: The aerial parts of F. subpinnata and the seeds of P. anisum were crushed separately followed by hydro-distillation method for 3 h using a Clevenger apparatus to obtain essential oils (EOs) and their constituents were analyzed by GC/MS. Also, the potential of antioxidant inhibitory of essential oils were determined using DPPH and FRAP methods. Results: p-Cymen-8-ol (51.13 %), α-terpinolene (7.69 %) and limonene (6.83 %) were the major components of F. subpinnata EO while trans-anethole (85.65 %) and carvone (5.31 %) were the major components in P. anisum EO. The results of antioxidant activities in DPPH and FRAP assays at the concentration of 250 μg/ml were 53.03 and 62.72 % for F. subpinnata and 50.27 and 59.91 % for P. anisum, respectively. The results of antioxidant activity by DPPH and FRAP methods indicated both essential oils had almost similar potential. Conclusion: Type and the amounts of the major components of the essential oils of F. subpinnata and P. anisum can be regarded as an accurate basis for differential diagnosing the plants. These differences can be used as a good phytochemical marker in correct identification and prevention of mistakes and deceptions in herbal products.